2004
DOI: 10.1016/j.jct.2004.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The low-temperature heat capacity of some lanthanide zirconates

Abstract: The heat capacities of the lanthanide zirconates Gd 2 Zr 2 O 7 and Eu 2 Zr 2 O 7 with pyrochlore structure were measured by adiabatic calorimetry and the hybrid adiabatic relaxation method in the temperature range (0.3 to 400) K. A thermal anomaly was observed for Gd 2 Zr 2 O 7 below T ¼ 15 K. From the measurements the thermodynamic functions of Gd 2 Zr 2 O 7 and Eu 2 Zr 2 O 7 were determined. By combining our results with the heat capacity data of La 2 Zr 2 O 7 , the lattice component of the heat capacity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 26 publications
5
40
3
Order By: Relevance
“…Recently, several theoretical studies [16][17][18] [24], and more recently Pr 2 Hf 2 O 7 [25] have shown that the Pr 3+ moment has a strong Ising character, described by a non-Kramers magnetic doublet. As in spin ice, no magnetic long-range ordering is observed down to dilution temperature, and magnetic specific heat shows a broad peak at about 2 K [21,22,[24][25][26][27], similar to what is observed in the classical spin ice Dy 2 Ti 2 O 7 .…”
Section: Introductionsupporting
confidence: 64%
“…Recently, several theoretical studies [16][17][18] [24], and more recently Pr 2 Hf 2 O 7 [25] have shown that the Pr 3+ moment has a strong Ising character, described by a non-Kramers magnetic doublet. As in spin ice, no magnetic long-range ordering is observed down to dilution temperature, and magnetic specific heat shows a broad peak at about 2 K [21,22,[24][25][26][27], similar to what is observed in the classical spin ice Dy 2 Ti 2 O 7 .…”
Section: Introductionsupporting
confidence: 64%
“…The solid and dashed curves correspond to the results of calculations based on the CF energies obtained in the present work and in Ref. [56], respectively.…”
Section: Crystal Field Parametersmentioning
confidence: 53%
“…Compounds with a positive Curie-Weiss temperature θ CW indicative of ferromagnetic interactions, along with a strong Ising-like anisotropy, are, a priori, possible QSI candidates. In this Letter, we focus on Nd 2 Zr 2 O 7 , which falls into this class, as shown by magnetization [6][7][8] and CEF studies [8,9]. Nd 2 Zr 2 O 7 stands out as a fascinating system because of an additional interesting property.…”
mentioning
confidence: 99%